Morphological change in the active participle and active participle in the Qur’anic text - Younis, Batool (Al-Adab Journal, 2024)
Derivatives are mentioned in the Qur’anic text in the form (participle participle), it was interpreted as meaning (passive participle), and derivatives were mentioned in the form (passive participle), it was interpreted to mean (the active participle), The apparent form is called (the relative to it), That is, it was modified from another origin in another form, and the other form was called (the one that is modified from), and it is absent from the text, although its meaning remains in the wording of the apparent formula (the one that is modified to), The reason for this, according to some scholars, is that the forms of the direct object stipulated in the speech did not agree with the correct standard linguistic rule, They interpret a number of alternatives, justifying this by the validity and agreement of those alternatives with the correct rule.This study aimed to demonstrate the correctness of the apparent linguistic use of the word in the Qur’anic text, as it is an authentic and eloquent text that no other text is equal to, and demonstrated its compatibility with the correct normative rule by adopting interpretations and semantic evidence according to scholars, The research explained that morphological modification occurs when both sides of the modification are present in the speech, So that the interpretation is not based on the unseen, which exposes the single formula in the text to a number of different meanings.